2022
DOI: 10.1093/ve/veac068
|View full text |Cite
|
Sign up to set email alerts
|

Integrated viral elements suggest the dual lifestyle of Tetraselmis spp. Polinton-like viruses

Abstract: In this study, we aimed at exploring horizontal gene transfer between viruses and Chlorodendraceae green algae (Chlorophyta) using available genomic and transcriptomic sequences for 20 algal strains. We identified a significant number of genes sharing a higher sequence similarity with viral homologues, thus signaling their possible involvement in HGTs with viruses. Further characterization showed that many of these genes were clustered in DNA regions of several tens to hundreds of kilobases in size, originally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In addition to pPolB and INT, Polintons typically encode a core set of conserved genes encoding homologs of dsDNA virus proteins involved in virion morphogenesis, such as adenovirus-like maturation protease (PRO), genome-packaging ATPase, and major and minor capsid proteins (MCPs and mCPs, respectively) ( Feschotte and Pritham 2005 ; Gao and Voytas 2005 ; Krupovic et al 2014 ; Krupovic and Koonin 2014 ; Koonin et al 2015 ; Krupovic and Koonin 2015 , 2016 ). Polintons generally occupy a low fraction of their host genome ( Novick et al 2011 ; Haapa-Paananen et al 2014 ; da Silva et al 2018 ; Shao et al 2019 ; Klai et al 2020 ; Barreat and Katzourakis 2021 ; Chase et al 2022 ; Bellas et al 2023 ); however, there are genomes with much higher occurrence, such as the excavate Trichomonas vaginalis where Polintons expanded to occupy more than 30% of the genome ( Feschotte and Pritham 2007 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pPolB and INT, Polintons typically encode a core set of conserved genes encoding homologs of dsDNA virus proteins involved in virion morphogenesis, such as adenovirus-like maturation protease (PRO), genome-packaging ATPase, and major and minor capsid proteins (MCPs and mCPs, respectively) ( Feschotte and Pritham 2005 ; Gao and Voytas 2005 ; Krupovic et al 2014 ; Krupovic and Koonin 2014 ; Koonin et al 2015 ; Krupovic and Koonin 2015 , 2016 ). Polintons generally occupy a low fraction of their host genome ( Novick et al 2011 ; Haapa-Paananen et al 2014 ; da Silva et al 2018 ; Shao et al 2019 ; Klai et al 2020 ; Barreat and Katzourakis 2021 ; Chase et al 2022 ; Bellas et al 2023 ); however, there are genomes with much higher occurrence, such as the excavate Trichomonas vaginalis where Polintons expanded to occupy more than 30% of the genome ( Feschotte and Pritham 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…A combination of inferred protein characteristics (the presence of genes encoding homologs of the MCP and mCP and the ATPase and PRO involved in capsid maturation) strongly supports this possibility ( Krupovic et al 2014 ; Krupovic and Koonin 2015 ). A dual capability as viruses and transposons ( Krupovic et al 2014 ; Krupovic and Koonin 2015 ; Chase et al 2022 ) would afford Polintons an ability to propagate both within and between genomes.…”
Section: Introductionmentioning
confidence: 99%
“…PLVs were discovered in metagenomes ( 18 ) and exhibit a particularly high degree of genetic diversity. Recently, it was shown that PLVs, MPEs, and virophages are much more prevalent in protist genomes that previously assumed ( 19 23 ).…”
mentioning
confidence: 87%